Genome-wide association studies of nasopharyngeal carcinoma in the Malaysian Chinese cohort using single genes, meta-analysis and pathway analysis approaches / Chin Yoon Ming - Chin, Yoon Ming (2017)
Nasopharyngeal carcinoma (NPC) is an epithelial squamous cell carcinoma on the mucosal lining of the nasopharynx with high incidence in the southern Chinese population. NPC is constantly linked to Epstein Barr virus (EBV) infection but its etiology remains elusive considering many carriers of EBV never develop NPC. Genetic factors play an important role in NPC susceptibility. This study set out to identify genetic variants linked to NPC susceptibility using a genome-wide association (GWAS) approach in the Malaysian Chinese. The GWAS encompasses single genes, meta-analysis with NPC cohorts from Taiwan and southern China and a pathway/gene set approach. In the single gene approach, GWAS results confirmed the association of HLA-A to NPC with the strongest signal detected in rs3869062 (P=1.73x10-9). Fine mapping revealed associations in the amino acid variants as well as its corresponding SNPs in the antigen peptide binding groove (PHLA-A-aa-site-99=3.79x10-8, Prs1136697=3.79x10-8) and T-cell receptor binding site (PHLA-A-aa-site-145=1.41x10-4, Prs1059520=1.41x10-4) of the HLA-A. HLA-A amino acid variants and SNPs were correlated with the effects of HLA-A*02:07. Results showed a protective trend towards NPC for HLA-A variants in the Malaysian Chinese, consistent with previous findings of HLA-A NPC association. Meta-analysis performed by combining results from NPC GWAS of Malaysia, Taiwan and southern China (2,152 cases; 3,740 controls) revealed 43 noteworthy findings outside the MHC region were identified and targeted for replication in a pooled analysis (4,716 cases; 5,379 controls). In the combined metaanalysis, rs31489, located within the CLPTM1L/TERT region on chromosome 5p15.33, was strongly associated with NPC (OR=0.81; P=6.3x10-13). Associations of previously reported NPC GWAS were also replicated, namely rs6774494 (P=1.5x10-12; located in the MECOM gene region), rs9510787 (P=5.0x10-10; located in the TNFRSF19 gene region), and rs1412829/rs4977756/rs1063192 (P=2.8x10-8, P=7.0x10-7, and P=8.4x10-7, respectively; located in the CDKN2A/B gene region). The TERT gene is important for telomere maintenance and is overexpressed in NPC. The EBV protein LMP1 has been reported to modulate TERT expression/telomerase activity in NPC. The findings suggest that factors involved in telomere length maintenance are involved in NPC pathogenesis. An integrated pathway approach was employed to identify dysregulated pathways linked to NPC. This approach combines imputation NPC GWAS data from a Malaysian Chinese cohort as well as published expression data GSE12452 from both NPC and healthy nasopharynx tissues. Results identified NPC association with the Gene Ontology (GO) axonemal dyenein complex pathway (PGWAS-GSEA=1.98x10-2; PExpr- GSEA=1.27x10-24; PBonf-Combined=4.15x10-21). This association was replicated in a separate cohort using gene expression data from NPC and healthy nasopharynx tissues (PAmpliSeq- GSEA=1.37x10-3). Loss of function in the axonemal dyenein complex causes impaired cilia function, leading to poor mucociliary clearance and subsequently upper or lower respiratory tract infection, the former of which includes the nasopharynx. Our approach illustrates the potential use of integrated pathway analysis in detecting gene sets involved in the development of NPC in the Malaysian Chinese cohort.